Categorization of small-scale biomass combustion appliances by characteristic numbers. (January 2021) - Feldmeier, Sabine; Schwarz, Markus; Wopienka, Elisabeth; Pfeifer, Christoph
Abstract: The market offers a broad range of different combustion appliances dedicated to residential heating with biomass. The effect of fuel properties on the formation of slag and emissions varies and the technology influences the impact to a certain extent. The applicability of biomass fuels is not only determined by operational settings but also by the design of boiler components as grate area and combustion chamber. Aspects as the fuel load on the grate, residence time, geometry of grate and combustion chamber design, as well as feeding and de-ashing influence the extent of slag formation and emission release. The determination of characteristic numbers by means of constructional measures allows a systematic comparison and - in a further step - an assessment/categorization of combustion technologies. After conducting a boiler survey relevant parameters regarding grate, combustion chamber, feeding, and ash removal were gathered. Characteristic numbers were specified in order to compare technological aspects. The results of this study allow the investigation of the influence of the combustion technology on the performance. They will assist the systematic and targeted design of small-scale boilers and the optimization of combustion appliances in future, especially when it comes to fuel-flexibility. Graphical abstract: Image 1 Highlights: Technology indexes developed for coal combustion were applied for biomass boilers. Data of 76 small-scale appliances were gathered to provide typical ranges of design. Grate load, design of feeding system and ash removal strategy depend on approved fuel. Results allow an investigation of technological influence on combustion process. Findings provide a basis for a systematic and targeted design of small-scale boilers.